2003
DOI: 10.1176/appi.ajp.160.7.1337
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Power of Peritraumatic Dissociation and Acute Stress Symptoms for Posttraumatic Stress Symptoms: A Three-Month Prospective Study

Abstract: These results support earlier findings that peritraumatic dissociative experiences and acute stress are robust predictors of PTSD. Such symptoms may be of use for identifying at an early stage individuals at highest risk of remaining symptomatic. Future studies should investigate the predictive power of specific peritraumatic and acute stress disorder symptom clusters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
96
1
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(114 citation statements)
references
References 10 publications
9
96
1
6
Order By: Relevance
“…Peritraumatic dissociation can be an independent predictor for disaster-related PTSD symptom severity a few months after a disaster (e.g., Birmes et al, 2003, Koopman et al, 1994Shalev, Peri, Canetti, & Schreiber, 1996). Correlations in our study between peritraumatic dissociation and psychological problems 2-3-weeks postdisaster are significant and strong: Pearson's correlation with the SCL-90-R was .59 and with the IES was .64.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peritraumatic dissociation can be an independent predictor for disaster-related PTSD symptom severity a few months after a disaster (e.g., Birmes et al, 2003, Koopman et al, 1994Shalev, Peri, Canetti, & Schreiber, 1996). Correlations in our study between peritraumatic dissociation and psychological problems 2-3-weeks postdisaster are significant and strong: Pearson's correlation with the SCL-90-R was .59 and with the IES was .64.…”
Section: Discussionmentioning
confidence: 99%
“…Birmes et al (2003) for example, found that peritraumatic dissociation and acute stress symptoms together accounted for 33% of the explained variance in PTSD symptoms after 3 months. Their statistics showed that acute stress symptoms were marginally better independent predictors than peritraumatic dissociation.…”
mentioning
confidence: 99%
“…However, there are some interesting parallels between the two constructs. Both peritraumatic dissociation (Birmes et al, 2003;Punamaki, Komproe, Qouta, Elmasri, & de Jong, 2005;Gershuny, Cloitre, & Otto, 2003;Tichenor, Marmar, Weiss, Metzler, & Ronfeldt, 1999;Spiegel, Koopman, Cardena, & Classen, 1996) and SIA (Nishith, Griffin, & Poth, 2002) have been found to predict PTSD status in trauma victims.…”
mentioning
confidence: 99%
“…Some researchers have suggested that these victims would like to avoid recalling traumatic events due to emotional distress such that these victims cannot completely report the traumatic event [70], and female victims in particular seem to have dissociative symptoms and adopt avoidance to cope with traumatic events [71]. Some researchers have shown that whether victims have dissociative symptoms is a major index of PTSD prediction [72,73]. According to the DSM-5 criteria [74] (APA, 2013), the original C3 criteria have been changed to be part of D (D1), which were called negative alterations in cognitions and mood.…”
Section: Discussionmentioning
confidence: 99%